(untitled) (International Journal of Plant Biology, 2018)
Melastoma malabathricum L. flowers are part of a plant that contains quercetin and kaempferol. Quercetin and kaempferol are useful for their antioxidant and anticancer properties. The flowering phase affects levels of quercetin and kaempferol. There are four phases of flower blooming: 1st bud phase (K1), 2nd bud phase (K2), 3rd bud phase (K3), and flower bloom (M). It remains to be determined which phase of Melastoma malabathricum L. flowering shows the highest levels of quercetin and kaempferol. Quercetin and kaempferol levels were measured using HPLC MS/MS. The measured quercetin levels of K1, K2, K3, and M phases, respectively, were: 19.47 μg/g, 17.78 μg/g, 31.2 μg/g, and 94.32 μg/g. Levels of kaempferol during K1, K2, K3, and M, respectively, were: 140.99 μg/g, 57.28 μg/g, 95.32 μg/g, and 349.37 μg/g.